Interlaminar fracture in woven carbon/epoxy laminates - Paulo N.B. Reis; José A.M. Ferreira; José D.M. Costa; António M. Pereira (Fracture and Structural Integrity)
This paper describes an experimental study developed to characterize the mode I and mode II fracture toughness of carbon/epoxy woven composites, using DCB and ENF tests, respectively. The laminates were manufactured using an epoxy resin and twelve woven balanced bi-directional layers of carbon fibres, all of them with the same orientation (0/90º). Significant instantaneous delaminations were observed particularly for the DCB specimen, which were responsible for an oscillatory behaviour of GI versus crack length. The maximum values obtained for GIC and GIIC were 281 and 1800 J/m2, respectively.